Nitrate-nitrogen concentration variationin groundwater flow in a paddy field - Mohamed Azwan, Mohamed Zawawi; Mohd Kamil, Yusoff; Hazilia, Hussain; Suhani, Nasir (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/